Business integration management using WebSphere BI modeler and monitor a real world case study - Gavin, Lee (Redbooks, 2004)
Integrating distributed business applications is no easy task. Managing a heterogeneous distributed real-time environment is equally challenging. Integrated business environments can process huge volumes of messages per day. Messages are published, routed, transformed and consumed. The integrated environment has to deal with exception handling, performance bottlenecks, and changes in the participating systems. Components are distributed across different machines in different locations. A Business Integration Management System addresses these requirements and provides the best approach or set of approaches that can be followed to manage an integrated business environment. This IBM Redbooks publication is a case study of a real-life, business process, re-engineering exercise. We follow the pilot phase of this exercise from the design of a solution to modeling of the complex business processes, building these processes, and deploying them to a run-time environment. We also address many of the issues that surround an undertaking such as this and follow up on the success of the pilot.